Kepemimpinan Visioner Dalam Meningkatkan Daya Saing Pendidikan Islam Tranformatif - Kustiono Kastaji; Prim Masrokan Mutohar; Agus Eko Sujianto (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2024)
The aim of writing this work is to analyze visionary leadership in increasing the competitiveness of transformative Islamic education. The library research method involves collecting and analyzing various relevant literature, such as books, scientific journals, articles and research reports that discuss visionary leadership, Islamic education and educational competitiveness. This research uses a qualitative descriptive approach to identify key findings, connect theory with practice, and develop recommendations for effective implementation in the context of Islamic education. The results of this work show that the low ranking of education in Indonesia reflects the gap in educational quality and requires effective and sustainable intervention. Improving teacher quality through training and certification programs is very important to increase educational competitiveness. Visionary leadership is needed to direct and motivate teachers, staff and students in achieving better educational goals. School principals must be able to formulate and communicate a realistic and strategic vision, as well as adapt to changes and future challenges. The government and education stakeholders need to work together to improve the quality of teachers and ICT facilities in schools. Support from parents and collaboration between government, schools and industry are very important to ensure education in Indonesia is relevant to current developments and community needs.